A method for preparing glass fiber reinforced modified nylon particles by using waste nylon clothes
Patent Information
- Application Number
- CN202611478327.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]其一,玻纤与尼龙基体界面结合力弱,应力传递效率低
[0031]1)本发明以6-氨基-4-甲基-2,5-吡啶二甲腈为起始骨架,经伯胺与环氧基的开环加成引入氮氧自由基,经氰基与乙醇胺的加成-闭环反应构建双噁唑啉结构,再经仲胺与环氧基的开环加成引入三甲氧基硅烷基团,得到氮氧自由基双噁唑啉硅烷剂。氮氧自由基双噁唑啉硅烷剂中的双噁唑啉环在熔融共混过程中与尼龙分子链末端的端羧基发生开环加成反应,将断裂的尼龙分子链重新连接,使废旧尼龙的分子量得到有效恢复,基体强度增加、分子链缠结密度恢复,有利于改善回收尼龙材料的常温缺口冲击韧性和低温抗脆断能力;三甲氧基硅烷基团与玻璃纤维表面的硅羟基发生水解缩合,形成稳定的硅氧共价键,将氮氧自由基双噁唑啉硅烷剂锚定于玻纤表面,另一端与尼龙分子链连接的该改性剂分子在玻纤与尼龙基体之间起到分子桥接作用,有助于提升玻纤与尼龙基体之间的界面结合力;氮氧自由基在加工和使用过程中持续捕获烷基自由基,抑制热氧降解链式反应,保护修复后的分子链免受再次降解。由此,本发明通过三甲氧基硅烷的锚定、双噁唑啉的扩链和氮氧自由基的抗氧相互配合,能够同时改善玻纤与尼龙基体的界面结合力、恢复废旧尼龙因热氧降解损失的分子量、抑制加工和使用过程中的进一步热氧降解,并改善回收尼龙材料的常温冲击韧性和低温冲击韧性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically, it relates to a method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing. Background Technology
[0002] Nylon fiber is a crucial raw material for the global textile industry, but the recycling rate of waste nylon clothing is extremely low. Large quantities of waste clothing end up in landfills or incinerators, causing both resource waste and environmental stress. After recycling and regranulation, the mechanical properties of the matrix of waste nylon clothing experience a significant decline. To compensate for the insufficient strength of recycled nylon, the industry typically adds glass fiber to the waste nylon recycling system for reinforcement and modification, thereby improving the strength and rigidity of the recycled materials.
[0003] However, existing glass fiber reinforced recycled nylon technology still has the following shortcomings:
[0004] Firstly, the interfacial bonding between glass fiber and the nylon matrix is weak, resulting in low stress transfer efficiency. This is because the inorganic hydrophilic surface of glass fiber is intrinsically incompatible with the organic polymer of recycled nylon, and the waste nylon has aged and deteriorated during long-term use, damaging the original interfacial coupling layer. Consequently, it is difficult to form an effective interfacial bond between the glass fiber and the nylon matrix, and stress cannot be effectively transferred from the matrix to the glass fiber. Therefore, the reinforcing effect of the composite material falls far short of expectations.
[0005] Secondly, nylon is prone to thermo-oxidative degradation during processing, and conventional antioxidants cannot provide continuous and effective protection. During the melt processing of nylon, it is susceptible to free radical chain thermo-oxidative degradation due to high temperature, oxygen, and shear. In addition, conventional small molecule antioxidants are easily lost through volatilization at processing temperatures. Repeated processing causes irreversible breakage of molecular chains, ultimately leading to a significant decrease in the molecular weight of nylon and a significant deterioration in the material's strength and toughness.
[0006] Third, recycled nylon has poor low-temperature toughness, and products made from it are prone to brittle fracture in cold environments. Due to the decrease in molecular weight, recycled nylon materials have a significantly reduced molecular chain entanglement density, which not only degrades the material's own strength and room-temperature impact performance, but also further restricts the movement of molecular chain segments in low-temperature environments, making it difficult to dissipate impact energy. This makes the material prone to brittle fracture and significantly deteriorates its low-temperature toughness.
[0007] To address the above-mentioned technical deficiencies, this invention provides a method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing. Summary of the Invention
[0008] The purpose of this invention is to provide a method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing, in order to solve the problems mentioned in the background art.
[0009] The objective of this invention can be achieved through the following technical solutions:
[0010] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0011] S1: 6-amino-4-methyl-2,5-pyridinedicarboxylonite is subjected to a ring-opening addition reaction with 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to obtain pyridinedicarboxylonite nitroxide radical;
[0012] The chemical reaction equation is:
[0013]
[0014] S2: Pyridinedicarboxynitrile nitroxide radicals are reacted with ethanolamine in the presence of a catalyst to undergo an addition-ring-closing reaction to obtain bisoxazoline nitroxide radicals;
[0015] The chemical reaction equation is:
[0016]
[0017] S3: Bisoxazoline nitroxide radicals are reacted with γ-(2,3-epoxypropoxy)propyltrimethoxysilane in the presence of a catalyst to obtain nitroxide radical bisoxazoline silane agent.
[0018] The chemical reaction equation is:
[0019]
[0020] S4: Nylon 6 recycled material obtained from pretreatment of waste nylon clothing is mixed with nitrile free radical bisoxazoline silane agent and lubricant, and then melt-blended and extruded. Alkali-free short glass fibers are added during the extrusion process to obtain glass fiber reinforced nylon granules.
[0021] Furthermore, the molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxylonitrile is 1.05 to 1.1:1.
[0022] Furthermore, the ring-opening addition reaction in S1 is carried out at a temperature of 60–80 °C for 6–8 h.
[0023] Furthermore, the molar ratio of pyridinedicarboxynitrile nitroxide radicals to ethanolamine is 1:3 to 5.
[0024] Furthermore, the catalyst for the addition-ring-closing reaction in S2 is anhydrous zinc acetate, and the amount of anhydrous zinc acetate is 1.5% to 2.5% of the mass of the pyridinedicarboxynitrile nitric oxide radical.
[0025] Furthermore, the addition-ring-closing reaction in S2 is carried out at a temperature of 120–125 °C for 4–6 h.
[0026] Furthermore, the molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.05 to 1.1.
[0027] Furthermore, the catalyst for the ring-opening addition reaction in S3 is triethylamine, and the amount of triethylamine used accounts for 1.5% to 4.5% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0028] Furthermore, the ring-opening addition reaction in S3 is carried out at a temperature of 60–80 °C for 4–8 h.
[0029] Furthermore, based on 100 parts of recycled nylon 6 material, the amount of nitrogen oxide free radical bisoxazoline silane agent added is 0.5 to 1.0 parts, the amount of lubricant added is 0.3 to 0.8 parts, the amount of alkali-free short glass fiber added is 20 to 40 parts, and the lubricant is calcium stearate.
[0030] The beneficial effects of this invention are:
[0031] 1) This invention uses 6-amino-4-methyl-2,5-pyridinedicarboxynitrile as the starting skeleton, introduces nitroxide radicals through ring-opening addition of a primary amine and an epoxy group, constructs a bisoxazoline structure through addition-ring-closure reaction of a cyano group and an ethanolamine, and then introduces a trimethoxysilyl group through ring-opening addition of a secondary amine and an epoxy group to obtain a nitroxide radical bisoxazoline silane agent. During melt blending, the bisoxazoline ring in the nitroxide radical bisoxazoline silane agent undergoes a ring-opening addition reaction with the terminal carboxyl groups at the ends of the nylon molecular chains, reconnecting the broken nylon molecular chains and effectively restoring the molecular weight of the waste nylon. This increases the matrix strength and restores the molecular chain entanglement density, which is beneficial for improving the room temperature notched impact toughness and low temperature resistance to brittle fracture of recycled nylon materials. The trimethoxysilyl group undergoes hydrolytic condensation with the silanol groups on the glass fiber surface to form stable silicon-oxygen covalent bonds, anchoring the nitroxide radical bisoxazoline silane agent to the glass fiber surface. The modifier molecule, with its other end connected to the nylon molecular chain, acts as a molecular bridge between the glass fiber and the nylon matrix, helping to improve the interfacial bonding force between the glass fiber and the nylon matrix. During processing and use, the nitroxide radicals continuously capture alkyl radicals, inhibiting the thermo-oxidative degradation chain reaction and protecting the repaired molecular chains from further degradation. Therefore, this invention, through the synergistic effect of trimethoxysilane anchoring, bisoxazoline chain extension, and nitric oxide free radical antioxidant, can simultaneously improve the interfacial bonding between glass fiber and nylon matrix, restore the molecular weight lost by waste nylon due to thermo-oxidative degradation, inhibit further thermo-oxidative degradation during processing and use, and improve the room temperature impact toughness and low temperature impact toughness of recycled nylon materials.
[0032] 2) In this invention, the pyridine ring acts as a rigid bridging framework connecting the bisoxazoline and nitroxide radicals. The lone pair electrons of the nitrogen atom on the pyridine ring can coordinate with trace amounts of copper, iron, and other transition metal ions remaining in waste nylon to form stable complexes. This passivates the catalytic activity of metal ions, inhibiting their catalytic effect on the oxidative cracking reaction of the nylon molecular chain. This reduces the additional free radicals generated by metal ion catalysis, lowers the burden of nitroxide radical consumption, and makes the antioxidant protection more durable and effective. Simultaneously, the rigid aromatic heterocyclic structure of the pyridine ring helps improve the heat resistance of the polymer. Detailed Implementation
[0033] The technical solutions of the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. Based on the embodiments in this application specification, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection claimed in this application.
[0034] The raw materials used in this invention are not particularly restricted in terms of their source; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.
[0035] Example 1
[0036] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0037] S1: Under nitrogen protection and anhydrous conditions, a solution of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radicals was added dropwise to a solution of 6-amino-4-methyl-2,5-pyridinedicarboxynitrile with stirring. After the addition was complete, the temperature was raised to 60°C and the reaction was stirred for 6 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The purified product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:2) to obtain pyridinedicarboxynitrile nitroxide radicals.
[0038] It should be further noted that: the 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical solution was prepared according to a volume ratio of 3 mL: 1 g of anhydrous ethanol to 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical; and the 6-amino-4-methyl-2,5-pyridinedicarboxylonite solution was prepared according to a volume ratio of 5 mL: 1 g of anhydrous ethanol to 6-amino-4-methyl-2,5-pyridinedicarboxylonite.
[0039] The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxynitrile is 1.05:1.
[0040] S2: Under nitrogen protection, pyridinedicarboxynitrile nitroxide radicals were mixed with ethanolamine and anhydrous zinc acetate catalyst, and the mixture was heated to 120°C and stirred for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, and dichloromethane and deionized water were added for extraction. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by silica gel column chromatography (eluent was a 1:1 volume mixture of ethyl acetate and petroleum ether) to obtain bisoxazoline nitroxide radicals.
[0041] The molar ratio of pyridinedicarboxylon nitroxide radicals to ethanolamine is 1:3, and the amount of anhydrous zinc acetate accounts for 1.5% of the mass of pyridinedicarboxylon nitroxide radicals.
[0042] S3: Under nitrogen protection and anhydrous conditions, a solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise to a bisoxazoline nitroxide radical solution with stirring, while simultaneously adding triethylamine as a catalyst. After the addition was complete, the temperature was raised to 60°C, and the reaction was stirred for 4 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 3:1) to obtain the nitroxide radical bisoxazoline silane.
[0043] It should be further noted that: the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution was prepared with an anhydrous toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 3 mL: 1 g; and the bisoxazoline nitroxide radical solution was prepared with an anhydrous toluene and bisoxazoline nitroxide radical in a ratio of 5 mL: 1 g.
[0044] The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.05, and the amount of triethylamine used accounts for 1.5% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0045] S4: Waste nylon clothing, whose main component is nylon 6, is pretreated to obtain recycled nylon 6 material. The recycled nylon 6 material, nitrile oxide free radical bisoxazoline silane agent, and lubricant calcium stearate are then mixed in a high-speed mixer for 5 minutes. The mixed material is then fed into the main feed port of a twin-screw extruder, while alkali-free short glass fibers are fed through the glass fiber port. The extruded material is water-cooled, air-dried, and pelletized to obtain glass fiber reinforced nylon granules.
[0046] Further explanation is needed regarding the pretreatment process of waste nylon clothing: Waste nylon clothing with nylon 6 as the main component is sorted to remove foreign objects such as metal zippers and plastic buttons, as well as identifiable cotton / polyester blended fabrics, to obtain coarse nylon clothing; the coarse nylon clothing is first crushed, then placed in an 85°C sodium hydroxide aqueous solution (sodium hydroxide mass fraction of 3%) and stirred and washed for 40 minutes, and then rinsed with clean water until neutral; the washed nylon fragments are placed in an extraction tank, and an extraction solution (a mixed solution of anhydrous ethanol and formic acid, wherein the volume fraction of formic acid is 3%) is added, and the mixture is soaked and extracted at 45°C for 18 hours; after draining the extraction solution, the garment is rinsed 3 times with clean water, dried, and then crushed a second time to obtain recycled nylon 6 material.
[0047] Of these, taking 100 parts of recycled nylon 6 material as an example, the amount of nitrogen oxide free radical bisoxazoline silane agent added is 0.5 parts, the amount of calcium stearate lubricant added is 0.3 parts, and the amount of alkali-free short glass fiber added is 20 parts. The temperature of each section of the barrel of the twin-screw extruder is set as follows: Zone 1 220℃, Zone 2 230℃, Zone 3 230℃, Zone 4 230℃, Zone 5 230℃, Zone 6 240℃, Zone 7 230℃, Zone 8 230℃, and Zone 9 220℃, and the main extruder speed is 300 r / min.
[0048] Example 2
[0049] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0050] S1: Under nitrogen protection and anhydrous conditions, a solution of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radicals was added dropwise to a solution of 6-amino-4-methyl-2,5-pyridinedicarboxylonitrile with stirring. After the addition was complete, the temperature was raised to 65°C and the reaction was stirred for 6.5 h. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The purified product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:2) to obtain pyridinedicarboxylon nitroxide free radicals.
[0051] It should be further noted that: the 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical solution was prepared according to a volume ratio of anhydrous ethanol to 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical of 3.5 mL: 1 g; and the 6-amino-4-methyl-2,5-pyridinedicarboxylonite solution was prepared according to a volume ratio of anhydrous ethanol to 6-amino-4-methyl-2,5-pyridinedicarboxylonite of 5.75 mL: 1 g.
[0052] The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxynitrile is 1.0625:1.
[0053] S2: Under nitrogen protection, pyridinedicarboxynitrile nitroxide radicals were mixed with ethanolamine and anhydrous zinc acetate catalyst, and the mixture was heated to 121.25℃ and stirred for 4.5 h. After the reaction was completed, the mixture was cooled to room temperature, and dichloromethane and deionized water were added for extraction. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by silica gel column chromatography (eluent was a 1:1 volume mixture of ethyl acetate and petroleum ether) to obtain bisoxazoline nitroxide radicals.
[0054] The molar ratio of pyridinedicarboxylon nitroxide radicals to ethanolamine is 1:3.5, and the amount of anhydrous zinc acetate accounts for 1.75% of the mass of pyridinedicarboxylon nitroxide radicals.
[0055] S3: Under nitrogen protection and anhydrous conditions, a solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise to a bisoxazoline nitroxide radical solution with stirring, while simultaneously adding triethylamine as a catalyst. After the addition was complete, the temperature was raised to 65°C, and the reaction was stirred for 5 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 3:1) to obtain the nitroxide radical bisoxazoline silane agent.
[0056] It should be further noted that: the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution was prepared according to a ratio of anhydrous toluene to γ-(2,3-epoxypropoxy)propyltrimethoxysilane of 3.5 mL: 1 g; and the bisoxazoline nitroxide radical solution was prepared according to a ratio of anhydrous toluene to bisoxazoline nitroxide radical of 5.75 mL: 1 g.
[0057] The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.0625, and the amount of triethylamine used accounts for 2.25% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0058] S4: Waste nylon clothing, whose main component is nylon 6, is pretreated to obtain recycled nylon 6 material. The recycled nylon 6 material, nitrile oxide free radical bisoxazoline silane agent, and lubricant calcium stearate are then mixed in a high-speed mixer for 5 minutes. The mixed material is then fed into the main feed port of a twin-screw extruder, while alkali-free short glass fibers are fed through the glass fiber port. The extruded material is water-cooled, air-dried, and pelletized to obtain glass fiber reinforced nylon granules.
[0059] Further explanation is needed regarding the pretreatment process of waste nylon clothing: Waste nylon clothing with nylon 6 as the main component is sorted to remove foreign objects such as metal zippers and plastic buttons, as well as identifiable cotton / polyester blended fabrics, to obtain coarse nylon clothing; the coarse nylon clothing is first crushed, then placed in an 85°C sodium hydroxide aqueous solution (sodium hydroxide mass fraction of 3%) and stirred and washed for 40 minutes, and then rinsed with clean water until neutral; the washed nylon fragments are placed in an extraction tank, and an extraction solution (a mixed solution of anhydrous ethanol and formic acid, wherein the volume fraction of formic acid is 3%) is added, and the mixture is soaked and extracted at 45°C for 18 hours; after draining the extraction solution, the garment is rinsed 3 times with clean water, dried, and then crushed a second time to obtain recycled nylon 6 material.
[0060] Of these, taking 100 parts of recycled nylon 6 material as an example, the amount of nitrile oxide free radical bisoxazoline silane agent added is 0.625 parts, the amount of calcium stearate lubricant added is 0.425 parts, and the amount of alkali-free short glass fiber added is 25 parts. The temperature of each section of the barrel of the twin-screw extruder is set as follows: Zone 1 225℃, Zone 2 235℃, Zone 3 235℃, Zone 4 235℃, Zone 5 235℃, Zone 6 245℃, Zone 7 235℃, Zone 8 235℃, and Zone 9 225℃, and the main extruder speed is 350 r / min.
[0061] Example 3
[0062] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0063] S1: Under nitrogen protection and anhydrous conditions, a solution of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radicals was added dropwise to a solution of 6-amino-4-methyl-2,5-pyridinedicarboxylonitrile with stirring. After the addition was complete, the temperature was raised to 70°C and the reaction was stirred for 7 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:2) to obtain pyridinedicarboxylonitrile nitroxide free radicals.
[0064] It should be further noted that: the 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical solution was prepared according to a volume ratio of anhydrous ethanol to 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical of 4 mL: 1 g; and the 6-amino-4-methyl-2,5-pyridinedicarboxylonite solution was prepared according to a volume ratio of anhydrous ethanol to 6-amino-4-methyl-2,5-pyridinedicarboxylonite of 6.5 mL: 1 g.
[0065] The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxynitrile is 1.075:1.
[0066] S2: Under nitrogen protection, pyridinedicarboxynitrile nitroxide radicals were mixed with ethanolamine and anhydrous zinc acetate catalyst, and the mixture was heated to 122.5℃ and stirred for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and dichloromethane and deionized water were added for extraction. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by silica gel column chromatography (eluent was a 1:1 volume mixture of ethyl acetate and petroleum ether) to obtain bisoxazoline nitroxide radicals.
[0067] The molar ratio of pyridinedicarboxynitrile nitroxide radicals to ethanolamine is 1:4, and the amount of anhydrous zinc acetate accounts for 2.0% of the mass of pyridinedicarboxynitrile nitroxide radicals.
[0068] S3: Under nitrogen protection and anhydrous conditions, a solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise to a bisoxazoline nitroxide radical solution with stirring, while simultaneously adding triethylamine as a catalyst. After the addition was complete, the temperature was raised to 70°C, and the reaction was stirred for 6 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 3:1) to obtain the nitroxide radical bisoxazoline silane agent.
[0069] It should be further noted that: the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution was prepared at a ratio of 4 mL to 1 g of anhydrous toluene; and the bisoxazoline nitroxide radical solution was prepared at a ratio of 6.5 mL to 1 g of anhydrous toluene.
[0070] The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.075, and the amount of triethylamine accounts for 3.0% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0071] S4: Waste nylon clothing, whose main component is nylon 6, is pretreated to obtain recycled nylon 6 material. The recycled nylon 6 material, nitrile oxide free radical bisoxazoline silane agent, and lubricant calcium stearate are then mixed in a high-speed mixer for 5 minutes. The mixed material is then fed into the main feed port of a twin-screw extruder, while alkali-free short glass fibers are fed through the glass fiber port. The extruded material is water-cooled, air-dried, and pelletized to obtain glass fiber reinforced nylon granules.
[0072] Further explanation is needed regarding the pretreatment process of waste nylon clothing: Waste nylon clothing with nylon 6 as the main component is sorted to remove foreign objects such as metal zippers and plastic buttons, as well as identifiable cotton / polyester blended fabrics, to obtain coarse nylon clothing; the coarse nylon clothing is first crushed, then placed in an 85°C sodium hydroxide aqueous solution (sodium hydroxide mass fraction of 3%) and stirred and washed for 40 minutes, and then rinsed with clean water until neutral; the washed nylon fragments are placed in an extraction tank, and an extraction solution (a mixed solution of anhydrous ethanol and formic acid, wherein the volume fraction of formic acid is 3%) is added, and the mixture is soaked and extracted at 45°C for 18 hours; after draining the extraction solution, the garment is rinsed 3 times with clean water, dried, and then crushed a second time to obtain recycled nylon 6 material.
[0073] Of these, taking 100 parts of recycled nylon 6 material as an example, the amount of nitrogen oxide free radical bisoxazoline silane agent added is 0.75 parts, the amount of calcium stearate lubricant added is 0.55 parts, and the amount of alkali-free short glass fiber added is 30 parts. The temperature of each section of the barrel of the twin-screw extruder is set as follows: Zone 1 230℃, Zone 2 240℃, Zone 3 240℃, Zone 4 240℃, Zone 5 240℃, Zone 6 250℃, Zone 7 240℃, Zone 8 240℃, and Zone 9 230℃, and the main extruder speed is 400 r / min.
[0074] Example 4
[0075] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0076] S1: Under nitrogen protection and anhydrous conditions, a solution of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radicals was added dropwise to a solution of 6-amino-4-methyl-2,5-pyridinedicarboxylonitrile with stirring. After the addition was complete, the temperature was raised to 75°C and the reaction was stirred for 7.5 h. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:2) to obtain pyridinedicarboxylon nitroxide radicals.
[0077] It should be further noted that: the 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical solution was prepared according to a volume ratio of anhydrous ethanol to 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical of 4.5 mL: 1 g; and the 6-amino-4-methyl-2,5-pyridinedicarboxylonite solution was prepared according to a volume ratio of anhydrous ethanol to 6-amino-4-methyl-2,5-pyridinedicarboxylonite of 7.25 mL: 1 g.
[0078] The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxynitrile is 1.0875:1.
[0079] S2: Under nitrogen protection, pyridinedicarboxynitrile nitroxide radicals were mixed with ethanolamine and anhydrous zinc acetate catalyst, and the mixture was heated to 123.75℃ and stirred for 5.5 h. After the reaction was completed, the mixture was cooled to room temperature, and dichloromethane and deionized water were added for extraction. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by silica gel column chromatography (eluent was a 1:1 volume mixture of ethyl acetate and petroleum ether) to obtain bisoxazoline nitroxide radicals.
[0080] The molar ratio of pyridinedicarboxylon nitroxide radicals to ethanolamine is 1:4.5, and the amount of anhydrous zinc acetate accounts for 2.25% of the mass of pyridinedicarboxylon nitroxide radicals.
[0081] S3: Under nitrogen protection and anhydrous conditions, a solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise to a bisoxazoline nitroxide radical solution with stirring, while simultaneously adding triethylamine as a catalyst. After the addition was complete, the temperature was raised to 75°C, and the reaction was stirred for 7 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 3:1) to obtain the nitroxide radical bisoxazoline silane agent.
[0082] It should be further noted that: the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution was prepared according to a ratio of anhydrous toluene to γ-(2,3-epoxypropoxy)propyltrimethoxysilane of 4.5 mL: 1 g; and the bisoxazoline nitroxide radical solution was prepared according to a ratio of anhydrous toluene to bisoxazoline nitroxide radical of 7.25 mL: 1 g.
[0083] The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.0875, and the amount of triethylamine used accounts for 3.75% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0084] S4: Waste nylon clothing, whose main component is nylon 6, is pretreated to obtain recycled nylon 6 material. The recycled nylon 6 material, nitrile oxide free radical bisoxazoline silane agent, and lubricant calcium stearate are then mixed in a high-speed mixer for 5 minutes. The mixed material is then fed into the main feed port of a twin-screw extruder, while alkali-free short glass fibers are fed through the glass fiber port. The extruded material is water-cooled, air-dried, and pelletized to obtain glass fiber reinforced nylon granules.
[0085] Further explanation is needed regarding the pretreatment process of waste nylon clothing: Waste nylon clothing with nylon 6 as the main component is sorted to remove foreign objects such as metal zippers and plastic buttons, as well as identifiable cotton / polyester blended fabrics, to obtain coarse nylon clothing; the coarse nylon clothing is first crushed, then placed in an 85°C sodium hydroxide aqueous solution (sodium hydroxide mass fraction of 3%) and stirred and washed for 40 minutes, and then rinsed with clean water until neutral; the washed nylon fragments are placed in an extraction tank, and an extraction solution (a mixed solution of anhydrous ethanol and formic acid, wherein the volume fraction of formic acid is 3%) is added, and the mixture is soaked and extracted at 45°C for 18 hours; after draining the extraction solution, the garment is rinsed 3 times with clean water, dried, and then crushed a second time to obtain recycled nylon 6 material.
[0086] Of these, taking 100 parts of recycled nylon 6 material as an example, the amount of nitrile oxide free radical bisoxazoline silane agent added is 0.875 parts, the amount of calcium stearate lubricant added is 0.675 parts, and the amount of alkali-free short glass fiber added is 35 parts. The temperature of each section of the barrel of the twin-screw extruder is set as follows: Zone 1 235℃, Zone 2 245℃, Zone 3 245℃, Zone 4 245℃, Zone 5 245℃, Zone 6 255℃, Zone 7 245℃, Zone 8 245℃, and Zone 9 235℃, and the main extruder speed is 450 r / min.
[0087] Example 5
[0088] A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing includes the following steps:
[0089] S1: Under nitrogen protection and anhydrous conditions, a solution of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radicals was added dropwise to a solution of 6-amino-4-methyl-2,5-pyridinedicarboxynitrile with stirring. After the addition was complete, the temperature was raised to 80°C and the reaction was stirred for 8 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:2) to obtain pyridinedicarboxynitrile nitroxide radicals.
[0090] It should be further noted that: the 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical solution was prepared according to a volume ratio of 5 mL to 1 g of anhydrous ethanol and 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical; and the 6-amino-4-methyl-2,5-pyridinedicarboxylonite solution was prepared according to a volume ratio of 8 mL to 1 g of anhydrous ethanol and 6-amino-4-methyl-2,5-pyridinedicarboxylonite.
[0091] The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxynitrile is 1.1:1.
[0092] S2: Under nitrogen protection, pyridinedicarboxynitrile nitroxide radicals were mixed with ethanolamine and anhydrous zinc acetate catalyst, and the mixture was heated to 125°C and stirred for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, and dichloromethane and deionized water were added for extraction. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by silica gel column chromatography (eluent was a 1:1 volume mixture of ethyl acetate and petroleum ether) to obtain bisoxazoline nitroxide radicals.
[0093] The molar ratio of pyridinedicarboxynitrile nitroxide radicals to ethanolamine is 1:5, and the amount of anhydrous zinc acetate accounts for 2.5% of the mass of pyridinedicarboxynitrile nitroxide radicals.
[0094] S3: Under nitrogen protection and anhydrous conditions, a solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise to a bisoxazoline nitroxide radical solution with stirring, while simultaneously adding triethylamine as a catalyst. After the addition was complete, the temperature was raised to 80°C, and the reaction was stirred for 8 hours. After the reaction was completed, the solvent was removed by vacuum distillation. The residue was extracted with ethyl acetate and deionized water. The organic phase was washed twice with deionized water and twice with saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The product was purified by silica gel column chromatography (eluent was a mixture of ethyl acetate and petroleum ether in a volume ratio of 3:1) to obtain the nitroxide radical bisoxazoline silane agent.
[0095] It should be further noted that: the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution was prepared with an anhydrous toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 5 mL: 1 g; and the bisoxazoline nitroxide radical solution was prepared with an anhydrous toluene and bisoxazoline nitroxide radical in a ratio of 8 mL: 1 g.
[0096] The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.1, and the amount of triethylamine used accounts for 4.5% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0097] S4: Waste nylon clothing, whose main component is nylon 6, is pretreated to obtain recycled nylon 6 material. The recycled nylon 6 material, nitrile oxide free radical bisoxazoline silane agent, and lubricant calcium stearate are then mixed in a high-speed mixer for 5 minutes. The mixed material is then fed into the main feed port of a twin-screw extruder, while alkali-free short glass fibers are fed through the glass fiber port. The extruded material is water-cooled, air-dried, and pelletized to obtain glass fiber reinforced nylon granules.
[0098] Further explanation is needed regarding the pretreatment process of waste nylon clothing: Waste nylon clothing with nylon 6 as the main component is sorted to remove foreign objects such as metal zippers and plastic buttons, as well as identifiable cotton / polyester blended fabrics, to obtain coarse nylon clothing; the coarse nylon clothing is first crushed, then placed in an 85°C sodium hydroxide aqueous solution (sodium hydroxide mass fraction of 3%) and stirred and washed for 40 minutes, and then rinsed with clean water until neutral; the washed nylon fragments are placed in an extraction tank, and an extraction solution (a mixed solution of anhydrous ethanol and formic acid, wherein the volume fraction of formic acid is 3%) is added, and the mixture is soaked and extracted at 45°C for 18 hours; after draining the extraction solution, the garment is rinsed 3 times with clean water, dried, and then crushed a second time to obtain recycled nylon 6 material.
[0099] Of these, taking 100 parts of recycled nylon 6 material as an example, the amount of nitrogen oxide free radical bisoxazoline silane agent added is 1.0 part, the amount of calcium stearate lubricant added is 0.8 parts, and the amount of alkali-free short glass fiber added is 40 parts. The temperature of each section of the barrel of the twin-screw extruder is set as follows: Zone 1 240℃, Zone 2 250℃, Zone 3 250℃, Zone 4 250℃, Zone 5 250℃, Zone 6 260℃, Zone 7 250℃, Zone 8 250℃, and Zone 9 240℃, and the main extruder speed is 500 r / min.
[0100] Comparative Example 1
[0101] The difference between this comparative example and Example 1 is that no nitroxide radical bisoxazoline silane agent is added in S4, while the remaining steps are the same as in Example 1.
[0102] Experimental Example 1
[0103] The glass fiber reinforced modified nylon particles obtained in Examples 1-5 and Comparative Example 1 were subjected to the following performance tests, and the test results are shown in Table 1.
[0104] (1) Tensile strength: The tensile strength was tested in accordance with GB / T 1040.2-2022 standard.
[0105] (2) Notched impact strength at 23℃: The notched impact strength of a simply supported beam was tested at 23℃, referring to GB / T 1043.1-2008 standard.
[0106] (3) Notched impact strength at -40℃: The notched impact strength of a simply supported beam was tested at -40℃, referring to GB / T 1043.1-2008 standard.
[0107] (4) Heat distortion temperature: The heat distortion temperature was tested using method A (1.80MPa bending stress) in accordance with GB / T 1634.2-2019 standard.
[0108] (5) Tensile strength retention rate after thermo-oxidative aging: According to GB / T 7141-2008 standard, the sample was aged in hot air at 120℃ for 500h and the tensile strength was tested. The ratio of the tensile strength after aging to the tensile strength before aging was calculated.
[0109] Table 1
[0110] Test Project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Tensile strength (MPa) 142 148 155 152 145 112 <![CDATA[23°C Notched Impact Strength (kJ / m 2 )]]> 13.8 14.5 15.2 14.8 14.0 8.5 <![CDATA[-40℃ notched impact strength (kJ / m 2 )]]> 6.8 7.2 7.8 7.5 7.0 4.2 Heat distortion temperature (1.80 MPa, °C) 158 162 168 165 160 175 Tensile strength retention rate (%) after 500 hours of thermo-oxidative aging at 120℃ 88 90 93 91 89 62
[0111] As shown in Table 1, the glass fiber reinforced modified nylon particles prepared by the method of the present invention in Examples 1-5 exhibit higher tensile strength, room temperature notched impact strength, low temperature notched impact strength, and tensile strength retention rate after thermo-oxidative aging, while showing a smaller decrease in heat distortion temperature. The properties of Comparative Example 1 are all lower than those of Examples 1-5, especially in terms of tensile strength and tensile strength retention rate after thermo-oxidative aging. This indicates that the present invention can effectively improve the interfacial bonding force, room temperature impact toughness, low temperature brittle fracture resistance, and thermo-oxidative aging resistance of recycled nylon materials, while maintaining the material's heat resistance relatively well.
[0112] The descriptions of the above embodiments are merely illustrative of the methods and core ideas of the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing glass fiber reinforced modified nylon granules using waste nylon clothing, characterized in that, Includes the following steps: S1: 6-amino-4-methyl-2,5-pyridinedicarboxylonite is subjected to a ring-opening addition reaction with 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to obtain pyridinedicarboxylonite nitroxide radical; S2: Pyridinedicarboxynitrile nitroxide radicals are reacted with ethanolamine in the presence of a catalyst to undergo an addition-ring-closing reaction to obtain bisoxazoline nitroxide radicals; S3: Bisoxazoline nitroxide radicals are reacted with γ-(2,3-epoxypropoxy)propyltrimethoxysilane in the presence of a catalyst to obtain nitroxide radical bisoxazoline silane agent. S4: Nylon 6 recycled material obtained from pretreatment of waste nylon clothing is mixed with nitrile free radical bisoxazoline silane agent and lubricant, and then melt-blended and extruded. Alkali-free short glass fibers are added during the extrusion process to obtain glass fiber reinforced nylon granules.
2. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The molar ratio of 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical to 6-amino-4-methyl-2,5-pyridinedicarboxylonitrile is 1.05 to 1.1:
1.
3. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The ring-opening addition reaction in S1 takes place at a temperature of 60–80 °C for 6–8 h.
4. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The molar ratio of pyridinedicarboxynitrile nitric oxide radicals to ethanolamine is 1:3 to 5.
5. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The catalyst for the addition-ring-closing reaction in S2 is anhydrous zinc acetate, and the amount of anhydrous zinc acetate is 1.5% to 2.5% of the mass of the pyridinedicarboxynitrile nitric oxide radical.
6. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The addition-ring-closing reaction in S2 takes place at a temperature of 120–125 °C for 4–6 h.
7. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The molar ratio of bisoxazoline nitroxide radical to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:1.05 to 1.
1.
8. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The catalyst for the ring-opening addition reaction in S3 is triethylamine, and the amount of triethylamine used accounts for 1.5% to 4.5% of the mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
9. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, The ring-opening addition reaction in S3 takes place at a temperature of 60–80 °C for 4–8 h.
10. The method for preparing glass fiber reinforced modified nylon particles using waste nylon clothing according to claim 1, characterized in that, Based on 100 parts of recycled nylon 6 material, the amount of nitrogen oxide free radical bisoxazoline silane agent added is 0.5 to 1.0 parts, the amount of lubricant added is 0.3 to 0.8 parts, the amount of alkali-free short glass fiber added is 20 to 40 parts, and the lubricant is calcium stearate.